Development of Thermoresponsive Composite Hydrogel Loaded with Indocyanine Green and Camptothecin for Photochemotherapy of Skin Cancer After Surgery - Yu-Hsiang Lee; Chieh-Lin Chung (Gels)
Skin cancer is the world’s fifth most diagnosed malignancy and is increasingly occurring in young adults. The elevated morbidity and mortality of skin cancer are known to be highly correlated with its frequent recurrence after tumor excision. Although regimens such as chemotherapy and/or immunotherapy are often administered following surgical treatments, the patients may suffer from severe side effects, drug resistance, and/or high cost during treatments, indicating that the development of an effective and safe modality for skin cancer after surgery is still highly demanded nowadays. In this study, an injectable and thermoresponsive hyaluronic acid/hexamethylene diisocyanate-Pluronic F127 block copolymer crosslinking composite hydrogel loaded with indocyanine green (ICG) and camptothecin (CPT), called ICHHPG, was developed for photochemotherapy of skin cancer after surgery. ICHHPG can be self-gelationed at 37 °C and stabilizes ICG in the gel matrix. Upon NIR exposure, ICHHPG can generate hyperthermia and consequently provide photothermal therapy when the ICG dosage is >5 μM. Furthermore, ICHHPG may provide a remarkably enhanced cancericidal effect compared to the equal concentration of free ICG (≤10 μM) or CPT (≤1000 μM) alone, and more than 95% of cancer cells can be destroyed as the intra-gel doses of ICG/CPT were elevated to 10/800 μM. Given the confirmed cytotoxicity together with its fluidic and thermoresponsive characteristics which are foreseeably favorable for wound coverage, the developed ICHHPG is highly applicable for use in skin cancer treatment after surgical excision.